THE POTENTIAL AREA FOR PELAGIC FISHING IS BASED ON THE PRODUKTIVITY OF CATCHING GILL NETS IN THE MARINE OF TANJUNG MUTIARA AGAM DISTRICT WEST SUMATRA PROVINCE - Astuti, Rahmayanti; Sari, T. Ersti Yulika; Usman, Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on September 6, 2018. The analysis used data obtained at the Fisheries and Fish Landing Base (PPI) Tiku Agam Regency, West Sumatra Province.Aimed to study to find out the optimum fishing efforts for pelagic fish in Tanjung Mutiara waters and knowing the environmental effect on catch of gillnet and to know the environmental variable that have biggest effect. Data collection uses survey methods. The results of this study indicate the maximum production amount in Tanjung Mutiara 6923,397tons/year with optimum fishing effort 16,048 trips/year. The results of measurements on Environmental parameters during the research, obtained a current velocity between 0.1-0.2 m / s, water’s temperatures between 280C - 300C, water’s pH between 7-8, water’s transparency between 28 cm - 34 cm and water’s salinity 300/00-330/00. From the results of the multiple regression analysis, the Determination Coefficient (r2) of 0.335, which means 33.5% of the catch amount can be explained by the five environmental parameters studied, while the remainder (100% -33.5% = 66.5%) is explained by other factors. The result of the research can be explained the variable of current velocity is the most contribute to the catch of 34.9% and the lowest contribution is salinity of 2.9%. Keywords: fishing effort, multiple regression analysis, Tanjung Mutiara waters